2021
DOI: 10.3390/nano11030734
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effective Nano-Sized Curcumin Delivery System with High Drug Loading Capacity Prepared via Flash Nanoprecipitation

Abstract: Flash nanoprecipitation (FNP) is an efficient technique for encapsulating drugs in particulate carriers assembled by amphiphilic polymers. In this study, a novel nanoparticular system of a model drug curcumin (CUR) based on FNP technique was developed by using cheap and commercially available amphiphilic poly(vinyl pyrrolidone) (PVP) as stabilizer and natural polymer chitosan (CS) as trapping agent. Using this strategy, high encapsulation efficiency (EE > 95%) and drug loading capacity (DLC > 40%) of CUR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A higher total flow rate (50 mL/min), representing a faster mixing, decreased the CUR encapsulation efficiency from 49% to 17% and loading efficiency from 11% to 5% compared with a lower total flow rate (10 mL/min). The reason is that the encapsulation/loading of CUR relies on a flash nanoprecipitation where the hydrophobic CUR was dissolved in the water-miscible 2-MI methanol solution and rapidly mixed with antisolvent (ZIN water solution) so that the nanoprecipitation happened and the precipitated CUR could be encapsulated by the synthesised ZIF-8 nanoparticles at the same time [ 80 ]. Therefore, an over-high total flow rate (higher than 50 mL/min) resulted in a very short mixing time (less than 0.7 ms), which was not enough for sufficient nanoprecipitation of CUR, leading to a relative low CUR encapsulation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…A higher total flow rate (50 mL/min), representing a faster mixing, decreased the CUR encapsulation efficiency from 49% to 17% and loading efficiency from 11% to 5% compared with a lower total flow rate (10 mL/min). The reason is that the encapsulation/loading of CUR relies on a flash nanoprecipitation where the hydrophobic CUR was dissolved in the water-miscible 2-MI methanol solution and rapidly mixed with antisolvent (ZIN water solution) so that the nanoprecipitation happened and the precipitated CUR could be encapsulated by the synthesised ZIF-8 nanoparticles at the same time [ 80 ]. Therefore, an over-high total flow rate (higher than 50 mL/min) resulted in a very short mixing time (less than 0.7 ms), which was not enough for sufficient nanoprecipitation of CUR, leading to a relative low CUR encapsulation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 7 , the sizes of Cur-loaded CS nanocomplex decreased from 400 nm to 190 nm when the Re ranged from 199 to 2385. It was observed that the particle size did not further decrease when the Re exceeded 1590, which was owing to the homogenous mixing in the FNC process when Re reaches a certain degree [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…CUR-loaded zein NPs solution (1 ml) was placed into a dialysis bag (MWCO 10 kDa) and immersed in PBS solution (19 ml) containing 1% sodium dodecyl sulfonate (SDS, w/v) at pH 7.4 or 5.0 and 37 C. 17,18 The drug release process was studied over at a specific time interval.…”
Section: In Vitro Release (Surfactant-assisted)mentioning
confidence: 99%